Peran Ikatan Pelajar Muhammadiyah (IPM) Dalam Pembentukan Akhlak Siswa di SMP Muhammadiyah 7 Medan - Hutauruk, Tasriansyah; Nasution, Wahyudin Nur; Nasution, Zulkipli (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the role of the Muhammadiyah Student Association (IPM) in shaping student morals at Muhammadiyah 7 Medan Junior High School, to determine the supporting and inhibiting factors of the Muhammadiyah Student Association (IPM) in shaping student morals at Muhammadiyah 7 Medan Junior High School, and to determine changes in the formation of student morals after actively organizing in the Muhammadiyah Student Association (IPM) Muhammadiyah 7 Medan Junior High School. This research uses qualitative research methods. Using a phenomenological approach with a type of field research (field reserch) with a descriptive analysis model, the data that researchers collect are in the form of words or narratives. Data collection techniques using observation, interviews and documentation. The results of this study are on the role of the Muhammadiyah Student Association in shaping students at SMP Muhammadiyahadiyah 7 Medan, namely the Muhammadiyah Student Association (IPM) teaches Islamic values sourced from the Qur'an and Hadith, which can directly shape student morals, such as honesty, trustworthiness, patience, and tawakal. This learning process that is integrated with religious teachings helps students to more easily understand and implement noble morals in everyday life. Then there are also several supporting and inhibiting factors, including a supportive environment and religious and social activities in the formation of student morals at SMP Muhammadiyah 7 Medan.